Análise dos padrões de movimento da coluna vertebral e dos joelhos durante atividade de manuseio de carga - Valente, Luciana do Socorro da Silva (2011)
Despite the intense automation of tasks, handling materials is often performed in occupational enviroment. The material handling can be defined as any activity that requires use of force to lift, lower, carry, push, pull and hold an object. The Manual Load Handling is a necessary operation for loading/unloading, especially in local production, delivery center and end users, and this is a problem because it causes body overload. It has been associated with the development of musculoskeletal disorders especially in the lumbar spine, followed by upper and lower limbs, causing changes in the configuration of the posture. The aim of this study was to analyze the patterns of movement of the spine and knees during manual material handling activity. The study included 37 subjects, young adults, healthy and asymptomatic. The motion of the trunk and knees were measured by the inclinometer and electrogoniometer, respectively. The subjects were informed about a activity simulated of handling, a load (15 kg) should be transported from a fixed height to three different heights, called: high, intermediate and low. The two boxes were handled commonly found in the work environment and specially developed two prototypes for testing, cardboard and plastic materials. The range of motion and handling time were analyzed using descriptive statistics. To analyze the difference of the amplitude of the spine and knees in different heights and types of box ANOVA was used and post hoc Bonferroni adjusted when necessary. In the first study, we analyzed the motion of the spine and knees during handling of the two boxes commonly found in the workplace. The results showed significant differences in range of motion of the spine and knees in each of the heights and for each type of box. However, for the motion of flexion/extension of the spine showed no statistical difference between the types of box. The motion of lateral deviation right/left were larger for the cardboard box. The range of motion of flexion/extension of the knees were influenced by the types of box, being larger for the right knee and more evident in the handling to the low surface. Therefore, it is concluded that the handling hights and the types of box significantly influenced the amplitude of motion of the spine and knees. The motion flexion/extension of the spine were not influenced by the types of box. However, the motion of lateral deviation right/left were larger for the cardboard box. The motion of flexion/extension of the knees were influenced by the types of box, with larger amplitudes for the left knee and pronounced handling for the low surface, The motion of the spine strategies were influenced by the motion of the knees only to the low surface, so there is simultaneous adjustment of these structures, with extension spine and flexion of the knees.